一個學校本位教師專業發展評鑑規準選擇的發展案例 Case Study on Choice of School-Based Teacher Evaluation Criteria for Professional Development - 潘文福 Pan, Wen-Fu (National Changhua University of Education, 2012)
本研究以宜蘭縣一所即將參與教師專業發展評鑑的國中為例，透過教師專業發展評鑑規準的蒐集、優先採用規準的選擇、規準重要性比較的層級分析，以及焦點團體座談等方式，由研究者協助個案學校發展符合自己學校需求的評鑑規準。由個案學校25 名教師所組成的焦點團體，選出曾憲政等學者發展之版本，接著再從該版本選出所欲採用的八個規準，並以層級分析法比較規準重要性，本研究依據八個選出規準的權重，發展為個案學校教師專業發展評鑑的檢核表。這種學校本位的評鑑規準選用程序，除了可以協助個案學校凝聚共識來發展學校本位評鑑規準外，也可以推廣成為一種協助學校選用評鑑規準的標準化輔助程序。 For this study, one junior high school in Yi-lan County that will participate in the Teacher Evaluation for Profession Development (TEPD) project was used as an example. Based on the collection, selection, and comparison of the evaluation criteria, the researchers chose a case school to develop school-based teacher evaluation criteria that employed the Analytical Hierarchy Process (AHP) and focus group discussions. There were 25 teachers, each of whom represented different roles, including administrative heads and general teachers. Selected teachers formed a focus group in the case school. After choosing their preferred evaluation version, they picked their preferred evaluation criteria from the questionnaires. We used the AHP method to compare the importance of their 8 chosen criteria. On the basis of the weighting of the eight criteria, the researchers developed a school-based project checklist for the case school. Most of the focus group members agreed that the project checklist could be viewed as a reference standard for evaluators or as a self-evaluation table for teachers who required evaluation. This selection process of school-based criteria for TEPD is not only able to help the case school integrate the various views regarding the decision of which TEPD criteria to use, but could also be developed into a standardized aid program for other schools that intend to adopt TEPD.